2016
DOI: 10.1021/acs.analchem.5b04468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Spatiotemporal Chemical Profiling of Individual Lipid Droplets by Hyperspectral CARS Microscopy in Living Human Adipose-Derived Stem Cells

Abstract: There is increasing evidence showing that cytosolic lipid droplets, present in all eukaryotic cells, play a key role in many cellular functions. Yet their composition at the individual droplet level and how it evolves over time in living cells is essentially unknown due to the lack of suitable quantitative nondestructive measurement techniques. In this work, we demonstrate the ability of label-free hyperspectral coherent anti-Stokes Raman scattering (CARS) microscopy, together with a quantitative image analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…2H). For example, coherent anti-stokes Raman scattering (CARS) microscopy has revealed that lipid droplets within human adipose-derived stem cells and microalgae have different lipid constituents (Cavonius et al, 2015;Di Napoli et al, 2016). Furthermore, in McArh7777 rat liver cells, lipid droplets are either enriched in TAG or cholesterol esters (Hsieh et al, 2012).…”
Section: Are All Lipid Droplets the Same?mentioning
confidence: 99%
“…2H). For example, coherent anti-stokes Raman scattering (CARS) microscopy has revealed that lipid droplets within human adipose-derived stem cells and microalgae have different lipid constituents (Cavonius et al, 2015;Di Napoli et al, 2016). Furthermore, in McArh7777 rat liver cells, lipid droplets are either enriched in TAG or cholesterol esters (Hsieh et al, 2012).…”
Section: Are All Lipid Droplets the Same?mentioning
confidence: 99%
“…After that both pulses propagated through another SF57 glass block before entering the microscope. This configuration was later adopted in many experiments . The major benefit of using a single sub‐10‐fs Ti:sapphire laser over a PCF pumped by Ti:sapphire is the flat and stable spectral phase and high output power.…”
Section: Broadband Cars Techniquesmentioning
confidence: 99%
“…As shown in Figure 2, most of the peaks in the fingerprint region (there are roughly 50 of them) are intrinsically quite weak, whereas the roughly five peaks of the CH stretch region (2800 to 3100 cm −1 ) are much stronger. For this reason, coherent Raman imaging studies (even spectroscopic CRI) have focused primarily on lipids and other species that have strong signals in the CH stretch region of the spectrum 3941 .…”
Section: Bodymentioning
confidence: 99%